2015
DOI: 10.1101/033266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated long-term recording and analysis of neural activity in behaving animals

Abstract: Addressing how neural circuits underlie behavior is routinely done by measuring electrical activity from single neurons in experimental sessions. While such recordings yield snapshots of neural dynamics during specified tasks, they are ill-suited for tracking single-unit activity over longer timescales relevant for most developmental and learning processes, or for capturing neural dynamics across different behavioral states. Here we describe an automated platform for continuous long-term recordings of neural a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 132 publications
4
69
0
Order By: Relevance
“…Errors are expected when these time-collapsed clusters overlap with one another, however. That said, because MountainSort can be run on overlapping sections of data, it is conceptually straightforward to include augmentations that link clusters across time slices using segmentation fusion based algorithms (Dhawale AK, 2015). Cases where clusters drift in and out of noise or other clusters are more problematic, both for MountainSort and for all other current approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Errors are expected when these time-collapsed clusters overlap with one another, however. That said, because MountainSort can be run on overlapping sections of data, it is conceptually straightforward to include augmentations that link clusters across time slices using segmentation fusion based algorithms (Dhawale AK, 2015). Cases where clusters drift in and out of noise or other clusters are more problematic, both for MountainSort and for all other current approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Manual sorting can have error rates in excess of 20% (Wood et al, 2004) and there is substantial variability in labeling across different sorting sessions (Harris et al, 2000; Pedreira et al, 2012; Rossant et al, 2016). Furthermore, the human spike sorter could never keep up with the increasing volume of data arising from increasingly large electrode arrays applied over increasingly long durations (Berenyi et al, 2014; Dhawale AK, 2015; Du et al, 2011; Lopez et al, 2016; Santhanam et al, 2007; Shobe et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Similar constraints are faced in several other fields of data-intensive biology, such as electron-microscopic connectomics, which also rely on manual operator curation 38 . Thus, while substantial developments have occurred to reduce the amount of manual operator time required for the sorting process 37, 39 , fully automatic systems are rarely applied in current practice. Fortunately, analyses comparing the decisions made by multiple expert operators have shown that their corrections of automatic cluster performance tend to be similar 17, 37 .…”
Section: Multichannel Electrophysiologymentioning
confidence: 99%
“…Sampling bias in extracellular electrophysiology can be ameliorated by performing non-stop chronic recordings, using fixed electrodes, over very long time periods: recording 24 hours/day for days or weeks can lead to sufficient spike numbers to define clusters even for cells of very low firing rate 39 .…”
Section: Multichannel Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation